2003
DOI: 10.1590/s0103-97332003000200042
|View full text |Cite
|
Sign up to set email alerts
|

Two-center electron-electron correlation within the independent event model

Abstract: The Independent Event Model (IEVM) is used to analyze collision processes for systems with three and four electrons, in situations where up to three active electrons are involved and dynamical correlation effects play a major role. The model is applied to single electron loss and loss-ionization processes. All the possible ionization mechanisms for both collision partners in each exit channel are considered, including antiscreening, which, in the IEVM, can be taken into account in a consistent way along all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The absolute cross sections for the multiple ionization of He, Ne, Ar, Kr and Xe atoms accompanied by the electron loss of the He + projectile are listed in tables A.1-A.5 as functions of the projectile energy. The data for He and Ne targets have already been published in graphical form in [80] and [8], respectively; for the sake of completeness, we present them here in tabular form.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absolute cross sections for the multiple ionization of He, Ne, Ar, Kr and Xe atoms accompanied by the electron loss of the He + projectile are listed in tables A.1-A.5 as functions of the projectile energy. The data for He and Ne targets have already been published in graphical form in [80] and [8], respectively; for the sake of completeness, we present them here in tabular form.…”
Section: Resultsmentioning
confidence: 99%
“…It should be mentioned that the sum of the partial cross sections presented here have already been used in [24] in their analysis of the antiscreening contribution to the projectile electron loss. Also, the data for the He and Ne targets have already been published in graphical form in previous works (see [80] for He and [8] for Ne). However, here they are also presented in tabular form and analysed using different approaches from those in the articles, in conjunction with the other targets.…”
Section: Introductionmentioning
confidence: 99%
“…Second, a full treatment requires in principle the inclusion of a dynamic electron-electron interaction (also called electron correlation) [24]. In ion-atom collisions, it has been shown that electron correlation has to be included in many cases in order to explain experimental cross sections [25][26][27][28][29]. For example, at low projectile energies, calculations clearly show that, even if the electron-electron interaction can be treated as a perturbation, its inclusion leads to large cross sections, up to a few 10 −17 cm 2 [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…(ii) The antiscreening process has an energy threshold similar to the one found in electron impact ionization [4,5,13]. The screening process is therefore, in principle, prominent below the antiscreening threshold.…”
Section: Introductionmentioning
confidence: 86%